2014
DOI: 10.1158/0008-5472.can-13-1703
|View full text |Cite
|
Sign up to set email alerts
|

RAE1 Ligands for the NKG2D Receptor Are Regulated by STING-Dependent DNA Sensor Pathways in Lymphoma

Abstract: The immunoreceptor NKG2D originally identified in natural killer cells recognizes ligands that are upregulated on tumor cells. Expression of NKG2D ligands (NKG2DLs) is activated by the DNA damage response (DDR) which is often activated constitutively in cancer cells, revealing them to natural killer cells as a mechanism of immunosurveillance. Here we report that the induction of retinoic acid early transcript 1 (RAE1) ligands for NKG2D by the DDR relies on a STING-dependent DNA sensor pathway involving the eff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
132
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 139 publications
(142 citation statements)
references
References 39 publications
7
132
1
2
Order By: Relevance
“…Increasing the intensity of the PicoGreen signal revealed weaker PicoGreen signals in the cytoplasm of A549 cells, which overlapped with MitoTracker staining ( Figure 3D). We previously found that blocking of the DDR resulted in the disappearance of dsDNA in the cytosol of Yac-1 cells (Lam et al, 2014). Similarly, inhibition of the DDR-initiating kinases ATM and ATR in A549 cells abrogated the cytosolic dsDNA staining ( Figure 3E).…”
Section: Partial Co-localization Of Cytosolic Dna With Late Endosomesupporting
confidence: 52%
See 4 more Smart Citations
“…Increasing the intensity of the PicoGreen signal revealed weaker PicoGreen signals in the cytoplasm of A549 cells, which overlapped with MitoTracker staining ( Figure 3D). We previously found that blocking of the DDR resulted in the disappearance of dsDNA in the cytosol of Yac-1 cells (Lam et al, 2014). Similarly, inhibition of the DDR-initiating kinases ATM and ATR in A549 cells abrogated the cytosolic dsDNA staining ( Figure 3E).…”
Section: Partial Co-localization Of Cytosolic Dna With Late Endosomesupporting
confidence: 52%
“…Constitutive Presence of DNA in the Cytosol of Several Human Cell Lines We previously found that ssDNA and dsDNA are constitutively present in the cytosol of the mouse lymphoma cell line Yac-1 (Lam et al, 2014) and Em-Myc B cell lymphomas (Figures 1C and S2A). To extend these observations to human cell lines, we stained the human lung carcinoma cell line A549, the acute monocytic leukemia cell line THP1, and the lung fibroblast cell line MRC5 for the presence of cytosolic ssDNA and dsDNA (Figures 1D,S2B,and S2C).…”
Section: Dna Damage Induces the Presence Of Cytosolic Dna In Tumor Cementioning
confidence: 91%
See 3 more Smart Citations